Caracterização de rotores adsortivos para composição de sistemas de climatização por adsorção - Melo, Francisco José Araujo (2015)
In this work, will be characterized two types of adsorptive wheels, an active effect and the other passive effect, known respectively as desiccant wheel and enthalpy wheel. These devices are used to compose the climatization adsorption systems as a means of promoting the dehumidification of air using the adsorption phenomenon that occurs in their adsorptive matrices. This phenomenon involves both the mass transfer and the heat, its cycles are defined by two processes taking place simultaneously, the adsorption and desorption. In the study, the characterization will boil down to assess the equipment in different working conditions with the main objective to achieve better dehumidification of air using the least amount of energy possible. Procedures were used for low air flow rates set in three categories: the process flow, which is the airflow to be treated, or dehumidified, a regeneration flow, which is the air stream in countercurrent flow desiccant rotor with process flow will serve as a means of maintaining the adsorptive cycle always performing heat exchange and mass, and the return flow, which flow against the enthalpy rotor will also serve as a means of promoting the dehumidification of process air. In the regeneration flow rates will be assessed the effects of low temperature heating and in both wheels will be evaluated the effects of different rotational speeds. Will also take place, procedures in order to verify the possibility of the wheel enthalpy work as a wheel desiccant . The findings contributed significantly to the climate control by adsorption systems is taken increasingly as a viable alternative to replacing conventional cooling.